GE_GERICHTE P/5390/2018 vom 25. September 2019 - GE Cour de justice (2019)
IN DUBIO PRO REO;DISPOSITIONS PÉNALES DE LA LSTUP;SÉJOUR ILLÉGAL | LSTUP.19.al1.letD; LSTUP.19A.al1; LEI.115.al1.letB; LEI.115.al3; CP.12.al3